Comparison Of The Influence Of Social Media Marketing Activities On Purchase Intention In Mediating Consumer Brand Engagement In Local And Global Sneakers Brands In Indonesia - Bilal Panji Prasetyo; Rita Komaladewi; Asep Mulyana (UNIVED Press, 2025)
The objective of this study is to analyse the impact of social media marketing activities (SMMA) on consumer brand engagement (CBE) on the social media of local and global sneakers brands on customer purchase intention, with CBE acting as a mediator. Data were collected from 400 social media followers of local and global sneakers in Indonesia. The data were analysed using PLS-SEM with multigroup analysis (MGA) to measure causal relationships between variables from two or more groups. This study found that SMMA has a positive effect on purchase intention both directly and indirectly. SMMA has an effect on CBE. There is a positive effect of CBE on purchase intention. There is no significant difference between local and global sneakers brands in Indonesia. It is recommended that those engaged in the sneakers business and online business managers pay attention to the factors that shape customer purchase intention. This can be achieved by paying attention to social media activities, which can be used to stimulate consumer relationships with brands that have an impact on purchase intention. This study proposes a new model for research in the field of fashion, especially sneakers, by using comparisons to find out the differences between local and global sneakers brands in Indonesia